Survey Evidence on Wage Rigidity and Unemployment: Sweden in the 1990s - Jonas Agell; Per Lundborg (Uppsala University, Department of Economics, 1999)
This study reports the results from a repeat survey among managers in Swedish manufacturing, designed to explore how a severe and prolonged macroeconomic shock affects wage rigidity and unemployment. Our second survey was conducted in 1998, when the unemployment rate was much higher, and the inflation rate much lower, than when we conducted the first survey in 1991. We find no evidence that the increase in unemployment has softened the mechanisms generating wage rigidity. On the contrary, we conclude that because of severe downward nominal wage rigidity real wages have become more rigid during Swedens move to a low-inflation environment. We also report a range of new evidence on underbidding, efficiency wage mechanisms, job security legislation, workers wage norms, and to what extent the long-term unemployed are subject to statistical discrimination.
urn:nbn:se:uu:diva-2455
Keywords: E24; J41; J63; 330; Unemployment; wage rigidity; repeat survey; recession; Lohnrigidität; Arbeitslosigkeit; Schock; Lohnbildung; Verarbeitendes Gewerbe